Pacific finance sector brief Papua New Guinea. (Metro Manila, Philippines Asian Development Bank, 2019)
Papua New Guineas finance sector is the most advanced among the Pacific developing countries. In addition to the usual institutions such as commercial banks and microfinance companies, it also has more complex entities such as superannuation funds, life insurance companies, and a stock exchange. Nevertheless, the size, composition, breadth, and diversity of the countrys financial services sector remains quite limited. Its geography and remoteness is a considerable challenge, as is its high levels of crime, corruption, and poor security. Finance sector growth can be stimulated if excessive regulations and high costs that hinder competition are addressed.
Keywords: Finance -- Papua New Guinea; Industrial policy; Electronic books